Gender and Communication Style: Overview on Face-to-Face Communication and Online Text (Whatsapp Group) - Alvin Afif Muhtar (LPPM IAIN Parepare, 2021)
This study aims to compare the styles of communication based on gender differences when communicating face-to-face and when communicating through whatsapp group media. The method used is a qualitative method with a case study approach. The data analysis used is interactive qualitative analysis, data presentation, drawing, conclusions and verification. The research subjects consisted of 10 students who were members of the whatsapp group